A Delivering OR Staff Beyond The Basic Orientation - Panneton, Yves (Operating Room Nurses Association of Canada Journal, 2001)
It is difficult, in the current context of staff shortage and financial restraints, to conduct staff development beyond the orientation. With one hour a week, a global vision and the combination of a few basic strategies, the perioperative educator can push the envelope.